2017
DOI: 10.12678/1089-313x.21.4.179
|View full text |Cite
|
Sign up to set email alerts
|

External Focus of Attention Enhances Children's Learning of a Classical Ballet Pirouette

Abstract: The purpose of the present study was to investigate the influence of instructions promoting an external versus internal focus of attention on the learning of a specific balance task, the pirouette en dehors (from fourth position), in 10-year-old novice ballet students. In addition, we sought to gain insight into learners' motivation and subjective learning experience as a function of different focus conditions. Thirty-eight children were randomly assigned to one of two groups. In the external focus (EF) group,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 25 publications
1
9
0
Order By: Relevance
“…In terms of attentional focus in pirouette performance, two studies examined the use of instructions that emphasized maintaining a visual reference point. Da Silva et al (2017) found that children with a visual instruction performed superiorly to children who were instructed to keep their head stable, in line with the current finding that head stabilization is perhaps a less important factor. However, with the inclusion of a control group, the study of Denardi and Corréa (2013) observed no advantage of instructions focusing on the head and vision.…”
Section: Discussionsupporting
confidence: 90%
“…In terms of attentional focus in pirouette performance, two studies examined the use of instructions that emphasized maintaining a visual reference point. Da Silva et al (2017) found that children with a visual instruction performed superiorly to children who were instructed to keep their head stable, in line with the current finding that head stabilization is perhaps a less important factor. However, with the inclusion of a control group, the study of Denardi and Corréa (2013) observed no advantage of instructions focusing on the head and vision.…”
Section: Discussionsupporting
confidence: 90%
“…Another aspect that needs to be discussed is that only seven studies included a control group and results of the studies are inconsistent. Most results indicate that instructions (either analogy instructions or with an internal or external focus of attention) are just as effective as the control condition (Chow et al, 2014;Perreault & French, 2016;Teixeira da Silva et al, 2017;Tse, 2017, and the acquitition phase of; Hadler et al, 2014). In contrast, Tse and Masters (2019) showed that all forms of instruction were more effective compared to the control condition, both during practice and retention.…”
Section: Using Implicit Methods To Improve Motor Performancementioning
confidence: 97%
“…The study of Perreault and French (2015) only showed better performance of the external focus group in one of the practice blocks. On the retention test, four studies consistently showed better performance of the external focus of attention groups compared to the internal focus of attention groups (Brocken et al, 2016;Hadler et al, 2014;Perreault & French, 2015;Teixeira da Silva et al, 2017) (and control group in the study of Hadler et al (2014)). In contrast, six studies did not show any differences between the groups (Agar et al, 2016;Chow et al, 2014;Emanuel et al, 2008;Krajenbrink et al, 2018;Perreault & French, 2016;Wulf et al, 2010).…”
Section: Implicit Vs Explicit (Practice-retention-transfer-realized Intervention)mentioning
confidence: 93%
See 2 more Smart Citations